Potential development of renewable hydrogen imports to European markets until 2030 - Veronika Lenivova (The Oxford Institute for Energy Studies, 2022)
This paper considers potential import routes for low-carbon and renewable hydrogen (H2) to main European markets like Germany. In particular, it analyses claims made by Hydrogen Europe and subsequently picked up by the European Commission in its Hydrogen Strategy that there will be 40GW of electrolyser capacity in nearby countries providing hydrogen imports to Europe by 2030. The analysis shows that by 2030, potential demand for H2 could be high enough to initiate some limited international hydrogen trade, most likely between European countries initially, rather than from outside Europe. Geographically, a northern hydrogen cluster around Netherlands and NW Germany will be more significant for hydrogen demand, while southern Europe is more likely to have surplus low cost renewable power generation. The paper considers potential H2 exporters to Europe, including Ukraine and North African countries (in line with the proposal from Hydrogen Europe) as well as Norway and Russia. (The research pre-dates recent political and military tensions between Russia and Ukraine which are likely to influence future development pathways). The supply cost of hydrogen in 2030 is predicted to be in a reasonably (and perhaps surprisingly) narrow band around exteuro3/kg from various sources and supply chains. The paper concludes that overall, while imports of hydrogen to Europe are certainly possible in the longer term, there are many challenges to be addressed. This conclusion supports the growing consensus that development of low carbon hydrogen, certainly within Europe, is likely to start within relatively local hydrogen clusters, with some limited bilateral trade.
Keywords: 330; energy security; Energy Transition; Europe; Hydrogen